Knowledge Sharing System Berbasis Web di Fakultas Teknik Universitas Bangka Belitung - Rodiatul Adawiyah; Elyas Kustiawan; Eka Sari Wijayanti (Jurusan Teknik Elektro, Universitas Bangka Belitung, 2022)
New lecturers must be quickly adapted to their work environment. Adaptation was difficult when colleagues did not provide space for discussion to the new lecturers. This condition occurred at the Faculty of Engineering Bangka Belitung University, with the planned to open a new study program, new lecturers had to be in a temporary homebase that was not their field. The expectation from the Dean was the existence of a knowledge sharing system that can be accessed anytime and anywhere by lecturers. But in reality, the knowledge sharing system still did not exist and knowledge sharing carried out manually by face-to-face meetings between lecturers and through Whatsapp groups. This research was conducted at the Faculty of Engineering, Bangka Belitung University. The knowledge sharing system methodology uses a combination of two methods, which are Socialization, Externalization, Combination, Internalization (SECI), and Knowledge Management Life Cycle. The result of this research was a development of web-based knowledge sharing system with an object-oriented approach which has been tested with black box testing and resulted as the system functions worked well.